Green vs. sustainability performance assessment: a case study of an office building in Putrajaya, Malaysia - Shari, Zalina; Soebarto, Veronica (2012)
Building performance assessment systems (BPASs) are emerging rapidly in many countries with different emphasis and scope of assessment. This paper seeks to find out whether a building design which scores high when assessed by an environmental-focused BPAS would also produce high scores if assessed by a BPAS which is based on a balanced and holistic concept of sustainability. Two BPASs were applied on a case study office building in Putrajaya, Malaysia, namely: 1) Singapore’s Green Mark Scheme, an existing environmental-focused BPAS actually used to rate the green performance of the case study building in reality; and 2) Malaysia Office Building Sustainability Assessment (MOBSA) framework, developed by the author in a three-year research as a means to assess the sustainability performance (environmentally, socially and economically) of office buildings in Malaysia. The study found that the building achieved a very high overall score in terms of its environmental design performance but scored lower when social- and economic-related criteria at the scale broader than the building itself were also taken into consideration and appropriately weighted. It appears that a more comprehensive BPAS, embracing the whole concept or three dimensions of sustainability, is crucial to be introduced and implemented in Malaysia, in priority to, or alongside with, single-dimensional BPASs.